Neverending treatment for autistic children? - Ribeiro, Jeanne Marie Costa; Gomes, Márcia Gaspar (Clinical Styles. The Journal on the vicissitudes of childhood, 1999)
Considering psychoanalysis as its main axis, the article brings some reflections built upon a daily institutional work with autistic and psychotic children. The authors emphasize the impasses they deal with at clinical work when considering the end of treatment.